Collaborative Public Management Governance in the Implementation of Communal-Based Green Economic Development in Jayapura Regency - Kendi, Ibrahim Kristofol (Journal Social Civilecial, 2025)
This research analyzes Collaborative Public Management (CPM) in the implementation of Jayapura Regency Regent Regulation Number 5 of 2021 concerning Communal-Based Green Economic Development. The research uses a qualitative approach with secondary data in the form of regulations, regional development planning documents, RKPD, Renja OPD, as well as documents related to village government and indigenous communities. The analysis uses Agranoff and McGuire’s four CPM activities, namely activating network, framing, mobilizing, and synthesizing. The research results show that policy implementation has adequate institutional foundations and actors but has not yet developed into integrated collaborative governance. In the activating network, strategic actors are available, but the involvement of traditional villages, Ondoafi, and universities is not yet fully institutionalized. Regarding framing, Perbup Number 5 of 2021 has provided a normative framework but has not yet produced a shared vision and understanding across sectors. In mobilizing, various programs and resources are available, but they are still being mobilized sectorally. Meanwhile, synthesizing has been supported by coordination forums, but has not resulted in integration of priorities, programs, resources, conflict resolution and joint evaluation. The research concludes that CPM in communal-based green economic development in Jayapura Regency is at the emerging collaborative management stage. Strengthening policy implementation needs to be directed at integrating actors, aligning goals, mobilizing joint resources, and developing collective decision-making and evaluation mechanisms.